(untitled) (Indian Journal of Animal Production and Management, 2014)
The present investigation was conducted in 32 oestrous periods from 20 swamp buffalo cows and 13 oestrous periods from 7 swamp buffalo heifers maintained at Livestock Research Station, Assam Agricultural University, Mondira to study the signs and intensity of oestrus of swamp buffaloes. The common signs in cows and heifers included hyperemia of vulval mucous membrane, genital mucous discharge, frequent urination, standing for mounting by teaser bull, allowing chin resting by teaser bull, swelling of vulva, allowing sniffing of vulva by herd mates or teaser bull and placid response of the animal to placing of palm of hand on rump. The incidences of intense, intermediate, weak and silent oestrus were 3.13, 53.13, 21.87 and 21.87 per cent respectively in buffalo cows and 15.38, 46.15, 23.08 and 15.38 per cent respectively in buffalo heifers.